Fanpage da rádio Unesp FM: convergência e interatividade em prol da cultura e cidadania - Versuti, Christiane Delmondes [UNESP] (2015)
This work refers to the research project Fanpage Unesp FM Radio: convergence and interactivity for culture and citizenship. This work began with literature in the literature on the literature on the topics media and citizenship; public communication; public radio; educational radio; radio and internet; media convergence and digital social media. The methodology for the study has fanpage content analysis of Unesp FM Radio; graphic analysis and tables generated by Facebook Insights and also interviews with employees of Unesp FM Radio. The aim of this study was to evaluate the fanpage of Unesp FM Radio as media support to the expansion of cultural and educational impact of the Issuer; analyze how is the interaction with listeners in the fanpage platform; highlight the importance of using media that allow more interaction with the audience; highlight the need for strategic management of the fanpage and provide support for the Radio UNESP can use this tool to promote education, culture and citizenship